Developmental study identifies the ages at which the processes involved in the perception of verticality and in postural stability occur. (17th October 2016) - Tringali, Margherita; Wiener‐Vacher, Sylvette; Bucci, Maria Pia
Abstract: Aim: The aim of this study was to understand the role played by visual information on the development of verticality and postural stability in healthy children. Methods: The study comprised 66 healthy children from 4.0 to 15.7 years of age. Postural performances were recorded with a TechnoConcept platform. At the same time, the children's perception of subjective visual vertical (SVV) was recorded while they adjusted a vertical fluorescent line, either in the dark or in the presence of perturbing visual stimuli. Two testing control conditions without an SVV task were also performed by all of the children: static posturographic recording with open eyes and closed eyes. Results: Postural measurements provided evidence of a correlation between the children's age and the tasks performed. Postural stability improved with age until eight to nine years, and SVV performance improved after 10–11 years. After these ages, postural and SVV capabilities did not change until at least 15 years of age. Conclusion: Our findings suggest that the maturation of cortical and central processes involved in both the perception of verticality and in postural stability took place during childhood. However, maturation occurred later for vertical perception, which could imply delayed maturation of sensory integration processes.